(untitled) (Jurnal Wahana Konseling, 2025)
This study aims to analyze the strategies used by teachers in overcoming mathematics learning difficulties in students with dyscalculia at SD Negeri Sumberadi 1 Yogyakarta, as well as identifying supporting and inhibiting factors in the application of these strategies. Dyscalculia is a learning disorder characterized by difficulty understanding numbers, operating arithmetic, and solving math problems. This research uses a descriptive qualitative method with a phenomenological approach. Data were collected through direct observation and in-depth interviews with grade III math teachers. The results show that teachers apply various strategies, such as individual and group counseling guidance, continuous assessment, creative learning methods such as icebreaking and learning through play, and the use of visual media to facilitate student understanding. The main supporting factors are the availability of learning facilities and the support of the school principal. Obstacles faced include limited learning time, low parental awareness of children’s needs, and a less conducive learning environment.